High Power and High Frequency Class-DE Inverters - De Vries, Ian Douglas (Department of Electrical Engineering, 2023)
This thesis investigates the various aspects of the theory. design and construction of a Class-DE type inverter and how these affect the power and frequency limits over which a Class-DE inverter can feasibly be used to produce AC (or RF) power. To this extent. an analysis of Class-DE operation in a half-bridge inverter is performed. A similar approach to Hamill [61 is adopted but a different time reference was used. This allows the concept of a conduction angle to b1: introduced and hence enables a more intuitive understanding of the. equations thereafter. Equations to calculate circuit element values LCR ne1wor'k are developed. The amount above the resonant frequency of the LCR network that the switching frequency must be in order to obtain the correct phase lag of the load current is shown. The effect of a non-linear output capacitance is studied, and equations are modified lo take this effect into account. It was found that a Class-DE topology offers a theoretical power advantage over a Clalls-E topology. However, this power advantage decreases with increasing frequency and is dependent on the output capacitance of the active switching devices. Using currently available MOSFETs, a Class-OE topology has a theoretical power advantage over a Class-E topology up to approximately 10MHz. However, the prac1ical problems of implementing a Class-DE invener lO work into the HF band are formidable. These practical problems and the extent to which they ltml! !he operating frequency and power of a Class-DE type inverter are investigated Guidelines to solving these practical problems are discussed and some novel soluuons are developed that considerably extend the feasible operating frequency and power of a Class-DE inverter. These solutions enabled a brc,adband design of the control circuitry. communication-link and gate-drive to be developed. Using these des[gns, a prototype broadband half-bridge inverter was developed which was capable of switching from 50k.Hz through to 6MHz. When operated in the Class-DE mode, the inverter was found to be capable of delivering a power output of over J kW from SOk.l-lz to 5Mllz with an efficiency of over 91 %. The waveforms obtained from the inverter clearly show Class-OE operation. The results of this thesis prove that a Class-DE series resonant inverter can produce. RF power up to a frequency of 5MHz with a higher combination of power and efficiency than any other present topology. The pracucal problems of even higher operaun& frequencies are discussed and some possible solutions suggested. The mismatched load tolerance of a Class-DE type inverter is briefly investigated. A Class-DE Lype inverter could be used for any applications requiring RF power in the HF band, such as AM or SW rransmirters, induction neating and plasma generators. The information presented in this thesis will be useful 10 designers wishing lo implement such an impeller. In add1non a Class-DE inverter could form the first stage of a highly efficient and high frequency DC-DC converter and the 1nformat1on presented here is directly applicable to such an application